O uso da RMN na caracterização e quantificação de metabólitos produzidos por microorganismos com potencial biotecnológico - Valente, Angela Maria Montes Peral (2007)
Nowadays, the microorganisms are responsible for the production of several antibiotics, immunosuppressant and antitumors, furthermore they are extremely important in industrial process. This work describes the production process and the isolation of the citrinin (234,6 mg/L) and of the mycophenolic acid (371,2 mg/L) with high purity levels in the process of extraction of a fermentation of 8 and 12 days respectively of a cultivation in liquid in Czapek medium enriched with 0,2% of extract of yeast utilizing the fungi Penicillium Catl1.1 and Penicillium sp. Casp5, isolated of the Coffea arabica L. after asepsis, as well, the development of an analytical methodology to quantify this compounds using the NMR. Additionally, on this work, we describe the isolation and the structural elucidation of an new alkaloid from prodiginine class with modification on ring (C), from an extract produced by Streptomyces violaceusniger violaceusniger actinomycete, isolated as an endophyte from Zea mays L. leaves and identified by Costa (2005), which was able to inhibit the growing of phytopatogens with economic value (Pythium aphanidermatum, Rhizoctonia solani, Sclerotinia sclerotiorum, Phytophthora parasitica e Fusarium moniliforme). Therefore, Finally, due to the results obtained during the execution of this work, is able to conclude that the Nuclear Magnetic Resonance, beyond be presented like an efficient analytic technique in the quantification of the citrinin and of the mycophenolic acid in the extract fungi, was fundamental in the monitoring and optimization of the conditions of extraction during the period of 20 days of fermentation. Like this, to NMR is a technique that will be utilized in the process production and optimization of the substances produced by microorganisms in industrial scale.